A Geochemical and Isotopic Investigation of Metasedimentary Rocks from the North Caribou Greenstone Belt, Western Superior Province, Canada - Duff, Jason (Université d'Ottawa / University of Ottawa, 2014)
The North Caribou Greenstone Belt (NCGB) lies at the core the granitoid-dominant North Caribou Terrane (NCT). Two sedimentary assemblages; the Eyapamikama (ELS) and Zeemal-Heaton Lake (ZHA) form the core of the NCGB. Geochemistry of garnets from the orogenic Au deposit at Musselwhite suggest that the auriferous fluids have a contribution of metamorphic fluids and mineralization consisted of prolonged, multi-stage periods. Chemical zoning suggests changes in the influx of chalcophile and lithophile elements and that Au/sulphide ratios during nucleation were lower relative to later growth events. Zircons from the ELS and ZHA suggest a c. 100 My hiatus in the onset of sedimentation, with the ZHA showing younger, “Timiskaming-type” ages. Age distributions from each assemblage reflect proximal, igneous sources. Nd isotopic compositions of the ZHA suggest a mixture of ancient and contemporaneous sources which are similar to external TTG rocks. Deplete mantle model ages of the ZHA rocks indicate a Mesoarchean inheritance.
Keywords: Archean; garnet geochemistry; detrital zircon; Nd isotopes; Orogenic Au; greenstone belts